Comparative Analysis of the Image of the Hawk and the Eagle (On the Example of T. Pulatov's "Property" and X. Dustmukhammad's "High Above The Rocks") (Global Scientific Review, 2023)
This thesis provides a comparative analysis of the images of hawk and eagle in the works of T.Pulatov "Property" and X.Dustmukhammad "High above the cliffs". The functions of these two characters within the framework of the work are scientifically substantiated and the similarities and differences are shown.